Mudanças e acontecimentos ao longo da vida: um estudo de representações sociais no contexto da saúde - Silva, Luípa Michele (2015)
The life course is marked by different events and social changes, such as retirement, marriage, birth of children, among others. As the aging period of life marked by many of them. The choice of social representations as a theoretical basis for this study due to the fact that this, enable the seizure of everyday knowledge emphasizing social cognitive dimensions on events and changes throughout life are important for health, socially contextualized in the eyes of employees from different groups age and, in the apprehension of meanings associated with «old» and «aged». Research has the objective of analyzing the changes and employees of health events in different age groups of seniors and identify the social representations of the «old» and «aged» in the various age groups. It is exploratory and cross-sectional surveys of repetition in a mixed approach, based on the theoretical framework of social representations. The data collection was carried out from two studies, using a semi-structured questionnaire consists of three parts: the first with issues and words of Free Association Test, with the inductors terms: «old» and «aged», considering social demographic variables. In the first study they were interviewed 632 employees and in the second study 200 participants. The collected data were processed with the help of Iramuteq software and interpreted subsidized in the theory of social representations and complemented by the Statistical Package for Social Sciences (SPSS) version 22.0, quantitative, generating three items: 1) changes and events Lifelong : a comparative study among older age groups; 2) Health Events and Their Characteristics in Senior Life Route and 3) Social Representations of Aging and Old in different age groups. The events and changes throughout life in different age groups pointed out the family as the primary concern. For terms inductors: old and older were associated with negative images in different age groups, thus revealing, dimensions: social, biological, cultural and psychological negative front of the aging, responsible for different positions with unfavorable elderly. These results may help in policy making and natural health practices in the field of aging.